Kritik Konsep Hadis Shahih dalam Perspektif Syi’ah - Al Hafidh Nasution (Universitas Islam Negeri Sumatera Utara, 2018)
This article in general attempts to expose the authenticity of the hadith among the Sunnis and Shiites. The muhaddissin have determined the authentic hadith criteria, but there is a difference of authentic hadeeth among the Sunnis and Shiites. Hence, research using the approach of the restricted narrative of the priest is interesting to be examined more deeply, since the impact of the concept they understand will result in the many Prophetic Hadiths in the Sunni scriptures will not be applicable to the law, because of their supposition Hadith is only accepted if it is backed up to the Imam who is ma'shum only, not from the path of Imamiyah. Unlike the Sunnis, the traditions of the hadith are preceded by the method of Jarh wa Ta'dil, if the narrators have the qualifcation to the flawless or defective manners, then the narrative is accepted even though it is derived from the fact that it is different from this Sunni understanding to be explained, with the purpose of knowing and understanding how the Hadith concept Shahih in the Shia view, which is then analyzed with their concepts in the books of the Shi'ite Hadith such as al Kafi by al, Kulaini Biharul an War, and so forth.